PANDEMI COVID-19 DAN RELEVANSINYA TERHADAP JUMLAH PERKARA PERCERAIAN DI PENGADILAN AGAMA MANNA KOTA MANNA, BENGKULU SELATAN - Wendi Parwanto; Desi Wahyuni; Dwi Sakti Muhammad Huda (Balai Diklat Keagamaan Medan, 2023)
The spread of Covid-19 has many impacts such as on health and other social dimensions. Everything seemed to get a butterfly effect from the Covid-19 pandemic. During the Covid-19 Pandemic era, the number of divorce cases at the Manna Religious Court increased compared to the previous year. This study uses a combination of field research for primary data and library research for secondary data with a descriptive-analytical approach. Thus, the study aims to determine the relevance of the increase in divorce cases in the Manna Religious Court to the Covid-19 pandemic. And can be used as a means of prevention (precautionary) against the emergence of problems in the household by efforts to improve harmony in the family in the era of the Covid-19 Pandemic. The results show that the divorce rate at the Manna Religious Court throughout 2020 is not affected by the Covid-19 Pandemic. This is because the main factor that causes divorce most often is the constant quarrels and disputes between married couples. In this case, it clearly happened or started long before the Covid-19 Pandemic hit this country.